Acoustic micro‐Doppler signal processing with foveated electronic cochlea. Issue 2 (1st January 2015) - Figliolia, T.; Murray, T.S.; Andreou, A.G.
Abstract : An architecture and its digital implementation using field programmable gate arrays of an electronic cochlea with an acoustic fovea and address event representation output are presented. The system is experimentally characterised with simple harmonic signals and employed to process signals from a micro‐Doppler sonar.